(untitled) (African Journal of Biomedical Research, 2020)
We report a case of 39-year-old male with unintentional chloroquine overdose without any suicidal intention. Marked QTc prolongation of 0.508sec was observed acutely though patient’s total ingested dose was lower than most fatal doses reported in literature. This range of QTc carries a predisposition to potentially fatal ventricular arrhythmias. Serial electrocardiograms (ECGs) demonstrated gradual return of QTc towards normal while patient was on observation without any indication for active intervention. We recommend that in the event of chloroquine overdose, close monitoring of the cardiovascular system should be done even in apparently stable individuals